Retrospective (2000-2009) Study of Newcastle Disease (ND) Cases in Avian Species in Maiduguri, Borno State, North Eastern Nigeria - Sadiq, M.A.; Nwanta, J.A.; Okolocha, E.C.; Tijjani, A.N. (International Journal of Poultry Science, 2010)
A case-control study on Newcastle Disease (ND) in avian species was conducted using ten year (from January 2000 to December 2009) clinic records of the avian Clinic of the ultramodern Veterinary Hospital Maiduguri. A total of four thousand six hundred and forty seven (4647) with mean of 38.40±4.391 (Mean±SE) cases of various diseases of avian species were presented to the ultramodern veterinary hospital Maiduguri within the ten year period. Out of these cases ND accounted for 2427 (52.23%), from which 811 (17.5%) were male while 1616 (34.7%) were female avian species. Local fowls (L/Fowls) accounted for 755 (46±9) of all the cases, of which 459 (60.8%) were ND cases. Out of 1293 (74±14) cases in layers 740 (57.2%) were ND while from 709 (27±5) cases recorded in broilers, ND accounted for 268 (37.8%). A total of the 186 (10±2) cases recorded in turkeys, 99 (53.2%) were ND. Out of the 26 (2±0) cases in peacocks, 10 (38.5%) were ND. A total of 76 (4±1) cases recorded in ducks, 19 (25.0%) were ND while out of 46 (3±1) cases in geese, ND accounted for 5 (10.9%) cases. From 753 (45±7) cases in cockerels, 447 (59.4%) were ND. From the total of 106 (6±1) cases recorded in ostriches, 61 (57.5%) were ND. Out of 7 (2±0) cases in African crowned cranes (Cranes), 3 (42.9%) were ND while from 91 (1±0) cases in pigeons, ND accounted for 7 (7.7%) cases. Out of 575 (31±6) cases of guinea fowl (G/Fowls), 306 (53.2%) were ND cases; out of 24 (2±0) cases in psittacines, 3 (12.5%) were ND cases. The distribution of ND among flock size of various avian species showed that flock size 1-50 had 623 (13.40) cases, 51-100 had 548 (11.79%); 101-150 had 595 (12.80%) while flock size 151 and above had 661(14.22%) cases. Newcastle disease among age groups of various avian species showed that birds within the age range of 0-9 weeks had 718 (15.45%), 10-19 weeks 958 (20.61%), 20 weeks and above 412 (8.86%) while 339 (7.29%) cases were birds of unknown age. In the year 2000, 144 (56.7) ND cases were recorded among various avian species, 99 (49.0%) 2001 while 95 (48.2%) in 2002. In the year 2003, 243 (56.2%) cases were ND, 271 (52.7%) in 2004, 265 (46.0%) in 2005, 470 (66.7%) in 2006, 355 (51.2%) in 2007, 242 (35.1%) and 243 (62.9%) in 2008 and 2009 were ND cases respectively. Seasonal peaks of ND cases were shown to occur in January, November and December while the trend for other months showed relative stability.